A Study of the Binding of Anionic Mordant Red7 in Two Different Cationic Solutions Using Absorption Spectroscopy - El-Dali, Abdelmeneim; El-Hashani, Ashraf; Elsherif, Khaled M; Alsherkcy, Sabrin (International Journal of Chemistry and Materials Research, 2015)
The interactions of anionic dye, Mordant Red7 with two different cationic ligands (ethanol amine and tallow amine) were studied in acidic aqueous solution using UV–VIS absorption spectroscopy. The dye interacts strongly with oppositely charged ligands. The results have shown that the maximum absorbance of the dye decreased gradually after addition of opposite charge ligand, and also shows the emergence a new absorption band. The new peak was attributed to the formation of dye aggregation by intermolecular forces such as hydrophobic forces attraction, Van der Waals forces and hydrogen bonds. The binding constant (Kc) values of the dye to cationic ligands have been determined by means of Benesi–Hildebrand equation. The magnitude of Kc is large for tallow amine 43.05 x 103mol-1 L compared to ethanol amine 1.245 mol-1 L. This is because; tallow amine able to self-assemble into micelles (surfactant) at a specific concentration called the critical micelle concentration (CMC), thereby, the dye binding to micelle of tallow amine surfactant. On the other hand “ethanol amine does not form micelles”. The standard free energy change ΔG◦ for ethanol amine and tallow amine for the complexation process have also been determined.